Exosomal cargo including microRNA regulates sensory neuron to macrophage communication after nerve trauma. Issue 1 (December 2017) - Simeoli, Raffaele; Montague, Karli; Jones, Hefin; Castaldi, Laura; Chambers, David; Kelleher, Jayne; Vacca, Valentina; Pitcher, Thomas; Grist, John; Al-Ahdal, Hadil; Wong, Liang-Fong; Perretti, Mauro; et al.
Abstract Following peripheral axon injury, dysregulation of non-coding microRNAs (miRs) occurs in dorsal root ganglia (DRG) sensory neurons. Here we show that DRG neuron cell bodies release extracellular vesicles, including exosomes containing miRs, upon activity. We demonstrate that miR-21-5p is released in the exosomal fraction of cultured DRG following capsaicin activation of TRPV1 receptors. Pure sensory neuron-derived exosomes released by capsaicin are readily phagocytosed by macrophages in which an increase in miR-21-5p expression promotes a pro-inflammatory phenotype. After nerve injury in mice, miR-21-5p is upregulated in DRG neurons and both intrathecal delivery of a miR-21-5p antagomir and conditional deletion of miR-21 in sensory neurons reduce neuropathic hypersensitivity as well as the extent of inflammatory macrophage recruitment in the DRG. We suggest that upregulation and release of miR-21 contribute to sensory neuron–macrophage communication after damage to the peripheral nerve. Exosomes are known to contain microRNAs (miRs). Here the authors show that dorsal root ganglion neurons release exosomes containing miR-21-5p, which contributes to inflammatory cell recruitment following peripheral nerve injury.